S‐ICD screening revisited: do passing vectors sometimes fail?. Issue 2 (26th December 2021) - Wiles, Benedict M.; Morgan, John M.; Allavatam, Venugopal; ElRefai, Mohamed; Roberts, Paul R.
Abstract: Introduction: Pre‐implant ECG screening is performed to ensure that S‐ICD recipients have at least one suitable sensing vector, yet cardiac over‐sensing remains the commonest cause of inappropriate shock therapy in the S‐ICD population. One explanation would be the presence of dynamic variations in ECG morphology that result in variations in vector eligibility. Methods: Adult ICD patients had a 24‐h ambulatory ECG performed using a digital Holter positioned to record all three S‐ICD vectors. Using an S‐ICD simulator, automated screening was then performed at one‐minute intervals. In vectors with a mean vector score > 100 (the accepted value for a passing vector when screened on a single occasion), the percentage of all screening assessments that passed, eligible vector time (EVT), was calculated. EVT was compared statistically to QRS duration, corrected time to peak T (pTc) and mean vector score. Results: Ambulatory monitoring was performed in 14 patients (mean age 63.7 ± 5.2 years, 71.4% male) with 42 vectors analysed. In 19 vectors the mean vector score was > 100. Within this "passing" cohort EVT varied between 42.7% and 100%. In 7/19 (37%) the EVT was <75%. A negative correlation was found between QRS duration and EVT (Pearson correlation ‐.60, p = .007). No correlation was found between EVT and mean vector score or pTc. Conclusion: Vector eligibility is dynamic. When "passing" vectors are subjected to repeated screening, 37% are found to be ineligible, more than a quarter of the time. Further investigation is required to determine the clinical significance of these findings.